THE IMPACT OF A HEALTHY LIFESTYLE AMONG STUDENTS ON THE QUALITY OF EDUCATION - Kushmatova Dildora Ergashevna; Olimjonova Faraxnoza Orifjonovna (Web of Journals Publishing, 2024)
This article explores the significant influence of a healthy lifestyle on the quality of education among students. It delves into the interconnectedness of physical activity, nutrition, and adequate sleep on academic performance and overall well-being. Through a comprehensive literature analysis, the study aims to identify key factors contributing to the positive impact of a healthy lifestyle on educational outcomes. The research employs various methods to analyze the relationships between lifestyle choices and academic achievements, providing valuable insights for educators, policymakers, and students alike.
Keywords: healthy lifestyle, students, education, physical activity, nutrition, sleep, academic performance, well-being, cognitive function.